Web search of software developers—Characteristics and tips - Szabó, B. Katalin (Frontiers in Education, 2022)
There is more and more software in the world and this software has to be developed. All the people who develop software can be regarded as software developers, not just the professionals. Naturally, they often perform web searches to support their development activity. The article, based on the pertinent literature and also on the author’s own experiences as a longtime software developer, discusses characteristics of software developers’ web searches and gives some recommendations and tips to increase the efficiency of their searches, especially complex, exploratory searches. To the author’s knowledge, no such summary combined with tips, aimed at software developers, has been published before. It has been written in the hope that software developers, such students and their teachers would find it useful.